FROM CLASSROOM TO CYBERSPACE: SOCIAL CONSTRUCTIVIST LEARNING IN VIRTUAL ENVIRONMENTS - Lorna M Dreyer (PUPIL: International Journal of Teaching, Education and Learning, 2025)
Over recent decades, the increasing digitalisation of society has significantly influenced the field of teaching and learning, positively contributing to the educational process. Digital technology is now recognised as essential components of pedagogical practices. Educators are progressively integrating these technologies into their instructional practices, while institutions have adopted guidelines to promote digital engagement. Despite their benefits, digital technologies pose challenges for educators in maintaining learning quality, highlighting the need to investigate students’ experiences to inform effective teaching. The research objective was to explore students’ experiences with an asynchronous online discussion. A postgraduate program transitioned from fully residential to a blended teaching and learning model. A blended approach involves thoughtful combination of face-to-face with online learning experiences. The primary challenge was to adapt learning activities to facilitate social constructivist learning within a virtual environment. The research question was formulated as: What are students’ experiences of an online discussion forum? This project was framed by Vygotsky’s socio-cultural theory. Vygotsky underscores the importance of social interaction and the use of cultural tools, such as language, to stimulate development and promote cognitive growth. The Integrated Learning Design Framework was used to design a meaningful learning opportunity for students. Students participated in an asynchronous online discussion forum. Their experiences were compared to traditional in-class discussions. Data was collected through an online survey and questionnaire, with qualitative content analysis identifying key themes. Findings indicate that while students appreciated the flexibility of asynchronous tools, they preferred face-to-face conversations. To enhance online social learning, it is suggested to incorporate synchronous online activities. Research outcome: The study concludes that the combination in online interactions is crucial for meaningful learning experiences.The rapid advancement of technology, particularly during and after COVID-19, continues to challenge the authenticity and credibility of online teaching, learning, and assessment in higher education institutions.